Industrial training report: Bahagian Penyelidikan & Jaringan Industri (PJI) Unit Creative Media & Technology (UCMT) Universiti Teknologi MARA (Kelantan) / Muhammad Nazrin Amin Rudin - Amin Rudin, Muhammad Nazrin (Perpustakaan Tengku Anis, 2016)
The purpose of this documentation is to report the activities done by the trainee during the industrial training for five months starting from August 1st 2016 until December 30th 2016 in the office of Pusat Penyelidikan & Jaringan Industri (PJI) department, Universiti Teknologi Mara (UiTM) Machang, under the supervision of Prof Madya Dr. Hj. Nik. Kamaruzaman. This documentation include clear explanation on daily tasks assigned to the trainee be part under unit of Creative Media Technology (UCMT), managed outdoor event and program, data key in, others outside project activities. The most essential part of the training is the trainee has been given to make a special project which is consigning to build a website for UCMT UiTM Machang branch. The objectives of the website are to represent the unit in online to public and to increase the work effectiveness among the unit. Opinion and recommendations regarding the industrial training were given in this documentation.